Inflammasome-Independent Role of NLRP3 Mediates Mitochondrial Regulation in Renal Injury - Kim, Su-Mi; Kim, Yang Gyun; Kim, Dong-Jin; Park, Seon Hwa; Jeong, Kyung-Hwan; Lee, Yu Ho; Lim, Sung Jig; Lee, Sang-Ho; Moon, Ju-Young (Frontiers in Immunology, 2018)
The NOD-like receptor family, pyrin domain containing-3 (NLRP3) inflammasome has been implicated in renal inflammation and fibrosis. However, the biological function of inflammasome-independent NLRP3 in non-immune cells is still unclear. We evaluated the role of inflammasome-independent NLRP3 in renal tubular cells and assessed the value of NLRP3 as a therapeutic target for acute kidney injury (AKI). Various renal tubular cell lines and primary cultured tubular cells from NLRP3 knockout (KO) mice were used for in vitro studies. We also tested the role of tubular NLRP3 in AKI with a unilateral ureter obstruction model (UUO). Hypoxia induced significant increase of NLRP3 independent of ASC, caspase-1, and IL-1β. NLRP3 in renal tubular cells relocalized from the cytosol to the mitochondria during hypoxia and bound to mitochondrial antiviral signal protein (MAVS). The deletion of NLRP3 or MAVS in renal tubular cells attenuated mitochondrial reactive oxygen species (ROS) production and depolarization of the mitochondrial membrane potentials under hypoxia. In response to UUO, NLRP3 KO mice showed less fibrosis, apoptosis, and ROS injury than wild type (WT) mice. Compared with WT kidney, mitophagy was up-regulated in NLRP3 KO kidney relative to the baseline and it was protective against AKI. Our results indicate that inflammasome-independent NLRP3 in renal tubular cells plays important role in mitochondrial ROS production and injury by binding to MAVS after hypoxic injury. This mitochondrial regulation in the absence of NLRP3 increases autophagy and attenuates apoptosis after UUO. We suggest that inflammasome-independent NLRP3 could be a therapeutic target of AKI to prevent the progression of chronic kidney disease.